Increased Interleukin-6 Activity Associated with Painful Chemotherapy-Induced Peripheral Neuropathy in Women after Breast Cancer Treatment. (21st July 2010) - Starkweather, Angela
Abstract : Accumulating evidence suggests that neural-immune interactions are involved in the development of painful chemotherapy-induced peripheral neuropathy, particularly through the increased release of proinflammatory cytokines. The purpose of this study was used to evaluate levels of interleukin [IL]-6 and IL-6 receptors in women with breast cancer after the conclusion of chemotherapy who either had painful symptoms of chemotherapy-induced peripheral neuropathy (CIPN group, N = 20 ) or did not experience CIPN symptoms (Comparison group, N = 20 ). CIPN participants had significantly higher levels of IL-6 and soluble IL-6R (sIL-6R) compared to women without CIPN symptoms (P < .001 for both). In addition, soluble gp130, which blocks the IL-6/sIL-6R complex from binding to gp130 within the cellular membrane, was significantly lower( P < .01 ) . Circulating concentrations of sIL-6R were inversely correlated with the density of IL-6R on the cell surface of monocytes in the total sample( r = − .614, P = .005 ) . These findings suggest that IL-6 transsignaling may be an important biological mechanism associated with the persistence of painful CIPN symptoms, with potential implications for symptom management and research.